Review of somatic cell nuclear transfer in pig - Suchitra Muenthaisong; Andras Dinnyes; Tshimangadzo Lucky Nedambale (African Journal of Pig Farming, 2018)
It is now more than 8 years, since the first cloned pig from nuclear transfer was reported. Success of somatic cell nuclear transfer (SCNT) in pig is still low compared to that in bovine. Embryonic and neonatal abnormalities of cloned piglets are probably a result of incorrect or incomplete reprogramming of the transferred donor cell nuclei. Recently, technical refinements have resulted in a considerable increase of SCNT efficiency. The current level of efficiency is already sufficient for special purposes with high scientific and commercial impact including xenotransplantation, generation of human disease models and for biomedical studies. In this paper, we review current pig cloning methodologies for the technical and potential applications.